Synthesis and Surface Morphology of The Precursors of the N-Alkylated Isoindigo - Sani Sarjadi, Mohd; Zabidi, Wahidah; Lin Wong, Xin; Er Tan, Shu (International Journal of Engineering and Technology, 2018)
Isoindigo has been longly applied as the dying agent and recently introduced as an electron accepting unit of the conjugated polymers. For the later purpose, the isoindigo was generally alkylated before undergone polymerization. The purity, chemical structure, and the surface morphology of the alkylated isoindigo and its precursors was confirmed and studied through the thin layer chromatography, FTIR, NMR and SEM. Based on the micrograms, the straw-liked regular structure of oxindole has been transformed into irregular box-shaped isoindigo when two oxindole were coupled with each other at the particular position.Â Â